ANALISIS PENERAPAN PENDEKATAN PEMBELAJARAN MENDALAM PADA MATA PELAJARAN IPAS DI SEKOLAH DASAR - Syam, Nur Fatimah; Farida Febriati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of the deep learning approach in Science and Social Studies (IPAS) learning in sixth-grade elementary school. The study employed a qualitative approach with a descriptive research design. The research subject was a sixth-grade elementary school teacher. Data collection techniques were conducted through observation and interviews to obtain information regarding the implementation of deep learning in IPAS instruction. The findings revealed that the teacher had implemented deep learning through various active learning methods, such as Problem-Based Learning (PBL), discussions, demonstrations, inquiry, and experiments. The learning process was connected to students’ daily lives, enabling students to become more active, enthusiastic, confident in asking questions, and better able to understand the learning materials. The use of instructional media, including learning videos, teaching aids, books, and interactive television, also contributed to improving students’ understanding. However, the implementation of deep learning still encountered several challenges, including limited instructional time and limited supporting learning media.Based on the findings, it can be concluded that the deep learning approach is capable of creating more active and meaningful IPAS learning and enhancing student engagement in the learning process.